High-strength corrosion-resistant hot-rolled stainless steel coated wire rod for bridge cable and preparation method of high-strength corrosion-resistant hot-rolled stainless steel coated wire rod
Through hot-rolled stainless steel cladding strip technology, combined with high-carbon steel core and 316L stainless steel cladding, the corrosion problem of large bridge cables in extreme environments is solved, high strength and corrosion resistance are improved, extended service life and reduced maintenance costs.
Patent Information
- Application Number
- CN202411699273.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
AI Technical Summary
Existing large bridge cables are prone to corrosion in extreme marine environments, resulting in bridge safety and service life problems. The existing anti-corrosion methods have limitations, and stainless steel cables are costly and insufficient mechanical properties.
Using hot-rolled stainless steel cladding strips, by combining high-carbon steel cores with 316L stainless steel cladding, the high strength of high-carbon steel and the high corrosion resistance of 316L stainless steel are used to form a high-strength, high corrosion resistance bridge cable material.
It achieves the improvement of high strength, corrosion resistance and soxantiticization rate, extends the service life of the cable, reduces maintenance costs, and improves the reliability of the bridge.
Smart Images

Figure CN119530670A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wire rod steel bar preparation, and in particular relates to a hot-rolled stainless steel coated wire rod for high-strength corrosion-resistant bridge cables and a preparation method thereof. Background Art
[0002] With the development of economy, the demand for land transportation facilities is growing, especially the construction of large bridges across rivers and seas. Among them, suspension bridges and cable-stayed bridges have become the main bridge types of long-span bridges in the world due to their advantages such as strong spanning capacity, light structural weight and material saving. In the design of these two bridges, the cable system plays a vital load-bearing role. However, these cables are prone to corrosion damage due to long-term exposure to extreme marine environments, which affects the overall safety and service life of the bridge. At present, in order to slow down the corrosion of steel wires, the main methods used include galvanizing steel wires and adding anti-corrosion grease, but these methods have certain limitations, such as coating damage and poor adhesion, and pure stainless steel wires have good corrosion resistance, but the cost is high and the mechanical properties are insufficient. Therefore, the development of a new type of stainless steel / carbon steel composite material, especially in the research of stainless steel composite wire rods, has become the key to solving the above problems. This composite wire rod uses stainless steel as a coating during the preparation stage, which not only improves the corrosion resistance of the wire rod, but also ensures the required mechanical properties, thereby effectively extending the service life of the bridge cable and reducing the maintenance cost, providing a new guarantee for the reliability of the bridge. Summary of the invention
[0003] In view of the deficiencies in the prior art, the first object of the present invention is to provide a hot-rolled stainless steel coated wire rod for high-strength and corrosion-resistant bridge cables. The hot-rolled stainless steel coated wire rod provided by the present invention has high strength, high toughness, high corrosion resistance and high troostitization rate.
[0004] The second object of the present invention is to provide a method for preparing hot-rolled stainless steel coated wire rod for high-strength corrosion-resistant bridge cables. The preparation method of the present invention is simple and controllable and suitable for large-scale production.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] The present invention discloses a hot-rolled stainless steel coated wire rod for high-strength and corrosion-resistant bridge cables. The hot-rolled stainless steel coated wire rod is composed of a high-carbon steel core and a stainless steel coating. The high-carbon steel core is composed of the following components by mass percentage: C: 0.79% to 0.86%, Si: 0.15% to 0.35%, Mn: 0.50% to 0.85%, P≤0.015%, S≤0.015%, Cr≤0.2%, Ni≤0.2%, and the rest is Fe and unavoidable impurities;
[0007] The stainless steel coating has the following composition by mass percentage: Cr: 16%-18%, Ni: 10%-14%, Mo: 2%-3%, C≤0.03%, Mn≤2%, Si≤1%, P≤0.045%, S≤0.03%, N≤0.1%, and the rest is Fe and unavoidable impurities.
[0008] The hot-rolled stainless steel coated wire rod provided by the present invention is composed of a SWRH82B high-carbon steel core and a 316L stainless steel coating, with good surface quality, no surface defects such as folding and dew point, and good coating uniformity. The high-carbon steel SWRH82B has a high carbon content, which makes the material have high strength and hardness, and is an ideal choice for building bridge cables. High strength means that the cable can withstand greater forces without breaking, increasing the stability and safety of the structure, and 316L stainless steel contains a higher proportion of chromium, nickel and molybdenum, which can significantly improve the corrosion resistance of the material. Especially in marine or saline environments, this stainless steel can effectively resist chloride corrosion, thereby extending the service life of the cable.
[0009] During the actual exploration process, the inventors also tried high-strength steels with other compositions such as SWRH72B, SWRH62B as core materials, and materials such as 2205, 2304, and 2507 as claddings, but the resulting products all had many performance defects.
[0010] In a preferred embodiment, the thickness of the stainless steel coating is 450-650 μm. If the thickness of the stainless steel coating is controlled within the above range, the final performance is optimal. If the stainless steel coating is too thick, the volume of the stainless steel will be too large, which will reduce the overall mechanical properties of the product and increase the cost. If it is too thin, it will not only reduce the corrosion resistance, but also make the stainless steel coating prone to cracking during the hot rolling process or in service, exposing the base material.
[0011] The invention discloses a method for preparing a hot-rolled stainless steel coated wire rod for high-strength and corrosion-resistant bridge cables. The method comprises the following steps: assembling a high-carbon steel round billet and a stainless steel pipe, and then welding the composite billet to obtain the composite billet. The composite billet is firstly preheated, and then the composite billet is sequentially hot-rolled, wire-spinning and cooled to obtain the hot-rolled stainless steel coated wire rod.
[0012] Preferably, the diameter of the high carbon steel round billet is 102-106 mm; the outer diameter of the stainless steel pipe is 114-116 mm, the wall thickness is 5-6 mm, and the difference between the inner diameter of the stainless steel pipe and the diameter of the high carbon steel round billet is ≤4 mm.
[0013] In the present invention, the sizes of the high carbon steel round billet and the stainless steel pipe are controlled within the above range, and the final performance is optimal. If the diameter of the high carbon steel round billet is too large, the deformation in the first few passes will be large, and the substrate and the coating have not yet achieved good metallurgical bonding quality in the first few passes. Large deformation is likely to cause uneven coating and other surface quality problems. If it is too small, the mechanical performance requirements of the product cannot be met. If the inner diameter of the stainless steel pipe is much larger than that of the high carbon steel round billet, it is not conducive to the metallurgical bonding of the coating and the substrate.
[0014] Further preferably, the high carbon steel round billet is obtained by removing oxide scale from a high carbon steel rough billet, and the thickness of the oxide scale is 4-8 mm.
[0015] In a preferred embodiment, the welding is performed by using vacuum electron beam welding technology to weld the ends of the two materials, thereby preventing air from entering the gap between the two materials.
[0016] In a preferred embodiment, the preheating temperature of the composite steel billet is 1020-1080° C., and the preheating time is 1.5 h to 2 h.
[0017] According to a preferred embodiment, during the hot rolling process, elliptical rollers and round-hole rollers are used alternately in sequence, with elliptical rollers being used for the first time and the number of passes being controlled to be an even number, and finally the round-hole roller is used to end the process.
[0018] In the present invention, in order to achieve effective metallurgical bonding between the coating material and the base material, elliptical rollers and round hole rollers are used alternately in sequence. The elliptical hole type can increase the deformation amount, so that the two materials can achieve better metallurgical bonding, and the round hole type can further control the shape and size of the material.
[0019] In a preferred solution, a horizontal-vertical alternating non-twisting rolling mill is used in the hot rolling process. In the entire hot rolling process of the present invention, the entire rolling line adopts a horizontal-vertical alternating rolling mill, and the rollers are arranged vertically and horizontally alternately, which can apply pressure in different directions and can control the shape and size of the material with high precision. Applying pressure in different directions can also make the coating more uniform and the performance more uniform. The continuous plastic deformation of the blank is achieved through continuous roller compressive stress, which can effectively optimize the internal structure of the composite wire rod and ensure the production of high-quality materials.
[0020] According to a preferred embodiment, the hot rolling is composed of four stages, namely, rough rolling, intermediate rolling, pre-finishing rolling and finishing rolling, and the number of passes in any stage is an even number, wherein the number of passes of the rough rolling is 4-6, and the total deformation is controlled to be 34-36% during the rough rolling; the number of passes of the intermediate rolling is 6-8, and the total deformation is controlled to be 53-55% during the intermediate rolling; the number of passes of the pre-finishing rolling is 6-8, and the total deformation is controlled to be 45-47% during the pre-finishing rolling; the number of passes of the finishing rolling is 4-6, and the total deformation is controlled to be 34-36% during the finishing rolling.
[0021] In the present invention, four stages of rolling are performed according to the above deformation, and the performance of the final composite material is optimal. Effective metallurgical bonding has not been achieved in the rough rolling stage, so the deformation of each pass should not be too large, otherwise the coating material and the base material are prone to slippage due to large deformation, which will bury hidden dangers for the metallurgical bonding quality of the subsequent composite surface. A certain metallurgical bonding has been achieved in the intermediate rolling stage, so the deformation of each pass is increased to further promote the bonding quality. The deformation of the subsequent pre-finishing rolling and finishing rolling passes is gradually reduced to avoid surface defects caused by excessive deformation of the material.
[0022] In a preferred embodiment, during the hot rolling, the starting rolling temperature is controlled to be 1000-1040°C, and the finishing rolling temperature is controlled to be 880-920°C.
[0023] In the hot rolling process of the present invention, it is only necessary to control the starting rolling temperature and the finishing rolling temperature. Finishing rolling is a key pass. When the finishing rolling temperature is too high, it will cause the grain coarsening of the material, thereby reducing the strength and toughness, and affecting the performance of the final product. In addition, under high temperature environment, the metal surface is easily oxidized, forming defects, affecting the surface quality of the product. Too high a temperature may also affect the metallurgical bonding of the composite interface, leading to interface weaknesses and affecting the overall performance. On the contrary, if the finishing rolling temperature is too low, the plasticity of the material will be reduced, increasing the forming difficulty during the rolling process during the finishing rolling pass, and may even cause cracking, thereby affecting the surface quality. At the same time, the stress release is uneven at low temperatures, increasing the risk of cracks or other internal defects.
[0024] In a preferred embodiment, the spinning temperature is 830-870° C. When the spinning temperature is controlled within the above range, the performance of the final composite material is optimal.
[0025] The preferred solution is that the cooling adopts the Stelmore air cooling line, the total length of the Stelmore air cooling line is 90-100m, the roller speed is controlled at 45m / min-55m / min, and when running from the starting position to 14-16m, 3 fans are configured, and the air volume of the 3 fans is 100%; when running from 14-16m to 33-37m, 4 fans are configured, and the air volume of the 4 fans is 75%; when running from 33-37m to 47-52m, 3 fans are configured, and the air volume of the 3 fans is 100%; from 47-52m to the end, the configured fans are not turned on.
[0026] In the present invention, the maximum air volume of the fan used is 186,000 m3 / h. When the air volume of the fan is 100%, the maximum air volume is 186,000 m3 / h, and when the air volume of the fan is 75%, the maximum air volume is 139,500 m3 / h.
[0027] In the process of cooling using the Stelmor air cooling line, from the starting position to the 14-16m stage, the wire rod temperature in this area is relatively high, and proeutectoid cementite is prone to appear during the cooling process. It is a brittle phase and has a greater impact on the mechanical properties of the product. Therefore, the air volume of the first three fans is 100%, so that the wire rod can be cooled quickly and the formation time of proeutectoid cementite is shortened. From 14-16m to 33-37m, this section is 19-21m. As the wire rod cools down and enters the phase change temperature range, the air volume of the fan in this section is reduced. The purpose is to keep the wire rod in the phase change temperature range as long as possible to give the troostite sufficient time to form, thereby increasing the troostitization rate.
[0028] In the present invention, since the surface of the SWRH82B high carbon steel core has a 316L stainless steel coating, the temperature of the SWRH82B high carbon steel core cannot be measured from the surface. By controlling the roller speed within the scope of the present invention and coordinating the adjustment of the air volume, the precipitation time of the proeutectoid cementite of the matrix SWRH82B material of the coated wire rod can be effectively shortened, and the troostite formation time can be increased, which can effectively reduce the precipitation of the proeutectoid cementite and increase the troostitization rate.
[0029] In a preferred solution, during the cooling, the heat preservation cover is fully opened and the Jialing device is 10%.
[0030] Principles and advantages
[0031] The hot-rolled stainless steel coated wire rod provided by the present invention is composed of a SWRH82B high-carbon steel core and a 316L stainless steel coating, with good surface quality, no surface defects such as folding and dew point, and good coating uniformity. The high-carbon steel SWRH82B has a high carbon content, which makes the material have high strength and hardness, and is an ideal choice for building bridge cables. High strength means that the cable can withstand greater forces without breaking, increasing the stability and safety of the structure, and 316L stainless steel contains a higher proportion of chromium, nickel and molybdenum, which can significantly improve the corrosion resistance of the material. Especially in marine or saline environments, this stainless steel can effectively resist chloride corrosion, thereby extending the service life of the cable. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a side view of a section taken from the hot-rolled stainless steel clad wire rod provided in Example 1.
[0033] Figure 2 This is an end view of the hot-rolled stainless steel coated wire rod provided in Example 1. From the figure, it can be seen that there is a SWRH82B high carbon steel core in the middle and a 316L stainless steel coating on the outer ring. DETAILED DESCRIPTION
[0034] Examples 1-5
[0035] (1) A hot-rolled stainless steel coated wire rod for high-strength and corrosion-resistant bridge cables. In this example, the size of the finished wire rod is 12.5 mm. Among the raw materials, the chemical composition of SWRH82B is composed of the following substances by weight percentage: C: 0.79% to 0.86%, Si: 0.15% to 0.35%, Mn: 0.50% to 0.85%, P≤0.015%, S≤0.015%, Cr≤0.2%, Ni≤0.2%, and the rest is Fe and impurity elements. The chemical composition of 316L is composed of the following substances by weight percentage: Cr: 16% to 18%, Ni: 10%-14%, Mo: 2%-3%, C≤0.03%, Mn≤2%, Si≤1%, P≤0.045%, S≤0.03%, N≤0.1%, and the rest is Fe and impurity elements.
[0036] (2) Billet assembly: The raw materials used include SWRH82B high carbon steel round billets with a diameter of 110 mm and 316L stainless steel pipes with an outer diameter of 116 mm and a wall thickness of 5 mm. First, the surfaces of the two materials are cleaned to remove scale and other impurities. Then, the cleaned high carbon steel round billets are inserted into the stainless steel pipes, ensuring precise centering. The assembled billets are placed in a vacuum chamber, vacuumed to remove the internal air, and then sealed at both ends using electron beam welding technology. This step ensures that the materials are tightly bonded during the hot rolling process to prevent oxidation or contamination.
[0037] (3) Billet heating: The billet is placed in a regenerative step-beam furnace for heating. The heating temperature is 1050°C and the heating time is 1.5 h.
[0038] (4) Rolling temperature: The hot rolling production line is divided into four stages: rough rolling, intermediate rolling, pre-finishing rolling and finishing rolling. The rough rolling stage includes 4 passes, using oval-round hole rollers for large deformation to initially shape; the total deformation is controlled to 35%, and the intermediate rolling stage is further plastically deformed through 6 passes to refine the size and material properties; the total deformation is controlled to 54% during intermediate rolling, and the pre-finishing stage is passed through 6 passes, using fine roll hole adjustment to improve surface quality; the total deformation is controlled to 46% during pre-finishing rolling, and the final finishing stage includes 4 passes to complete the final size fine adjustment and performance optimization of the material, and the total deformation is controlled to 35% during finishing rolling. The entire rolling line adopts horizontal-vertical alternating non-twist rolling mill technology, and the oval rollers and round hole rollers are used alternately throughout the process. The continuous plastic deformation of the billet is achieved through continuous roller compressive stress, which can effectively optimize the internal structure of the composite wire rod, and improve its coating uniformity and overall performance, ensuring the production of high-quality materials to meet the strict requirements of practical applications. The measured rolling temperatures of the five embodiments are shown in Table 1.
[0039] Table 1 Measured rolling temperature
[0040] Example No. Initial rolling temperature (℃) Finishing rolling temperature (℃) 1 1025 912 2 1024 908 3 1023 888 4 1025 890 5 1023 915
[0041] (5) Spinning temperature: The measured spinning temperatures of five examples are shown in Table 2 below.
[0042] Table 2 Measured spinning temperature
[0043] Example No. Spinning temperature (℃) 1 855 2 853 3 836 4 845 5 858
[0044] (6) Wire rod cooling: The roller speeds and the parameters of the fans, heat preservation covers and Jialing devices in the five examples of the Stelmore air cooling line are shown in Table 3 below. The total length is 95 meters, divided into 11 sections, the entrance section, 9 middle sections (the average length of each section is 9.8-10.2 meters, and each section is equipped with 2 fans), and the exit section. 18 fans are configured. The fans are not dynamically adjusted. The wind speed of the first three fans is 100% throughout the entire process (from entering the roller to 14-16 meters from the roller entrance), the 4th to the 7th fans are 75% (a total of 19-21 meters, i.e. 14-16 meters to 33-37 meters), the 8th to the 10th fans are 100%, and the remaining fans are not turned on.
[0045] Table 3 Stelmore air cooling line parameters
[0046]
[0047] Comparative Example 1
[0048] The other conditions were the same as those in Example 1, except that the coating material was 2205. As a result, the surface quality had problems and dew point defects appeared in the coating.
[0049] Comparative Example 2
[0050] Other conditions were the same as those in Example 1, except that the total deformation during rough rolling was controlled to 48%. As a result, since the cladding and the substrate were not metallurgically bonded before rough rolling, excessive deformation during the rough rolling stage directly caused the cladding to fall off and the rolling failed.
[0051] Comparative Example 3
[0052] The other conditions were the same as those in Example 1, except that the total deformation of the rough rolling was controlled at 40%. As a result, the uniformity and surface quality of the coating were greatly affected. The coating was very uneven and many dew point phenomena occurred.
[0053] Comparative Example 4
[0054] Other conditions were the same as those in Example 1, except that the air volume of the fan was 100% throughout the entire process. As a result, the troostitization rate was reduced, resulting in a certain reduction in the tensile strength.
[0055] Performance testing:
[0056] The 5 embodiments and 4 comparative examples produced by this solution were tested for tensile strength, cross-sectional shrinkage, troostitization rate and coating thickness. For the detection of the four items, 5 samples were tested for each embodiment. The data in the following table are the average values of the 5 samples of each embodiment. It should be pointed out that when testing the coating thickness, the coating thickness at three points of each sample was tested and the average value was taken. The average value of the coating thickness of the 5 samples of each embodiment was taken again to obtain the final result recorded in the following table. The test results are shown in Table 4 below.
[0057] Table 4 Performance test results of the embodiments and comparative examples
[0058]
[0059] From the test results, it can be found that the coated wire rod produced by the solution of the patent of the present invention, after adding a layer of 316L stainless steel coating, its tensile strength, cross-sectional shrinkage rate and troostitization rate are all excellent, which can effectively meet the actual needs. At the same time, the coating thickness is basically maintained at 550μm±100μm, and there is no dew point phenomenon (i.e., defects in the coating and exposure of the internal high-carbon steel matrix), which greatly improves the corrosion resistance of the product. These characteristics make the coated wire rod of the present invention not only suitable for the key structure of steel wire for bridge cables, but also can significantly extend its service life and reduce the cost of anti-corrosion maintenance. Therefore, it has important industrial application value and broad market prospects.
Claims
1. A hot-rolled stainless steel coated wire rod for high-strength and corrosion-resistant bridge cables, characterized in that: The hot-rolled stainless steel coated wire rod is composed of a high carbon steel core and a stainless steel coating, wherein the high carbon steel core is composed of the following by mass percentage: C: 0.79% to 0.86%, Si: 0.15% to 0.35%, Mn: 0.50% to 0.85%, P≤0.015%, S≤0.015%, Cr≤0.2%, Ni≤0.2%, and the rest is Fe and unavoidable impurities; The stainless steel coating has the following composition by mass percentage: Cr: 16%-18%, Ni: 10%-14%, Mo: 2%-3%, C≤0.03%, Mn≤2%, Si≤1%, P≤0.045%, S≤0.03%, N≤0.1%, and the rest is Fe and unavoidable impurities.
2. The hot-rolled stainless steel coated wire rod for high-strength and corrosion-resistant bridge cables according to claim 1 is characterized in that: The thickness of the stainless steel coating is 450-650 μm.
3. The method for preparing a hot-rolled stainless steel coated wire rod for high-strength corrosion-resistant bridge cables according to claim 1 or 2, characterized in that: After assembling the high carbon steel round billet and the stainless steel pipe, a composite billet is obtained by welding, the composite billet is preheated, and then the composite billet is sequentially hot rolled, wire-spinning and cooled to obtain the hot rolled stainless steel clad wire rod.
4. The method for preparing a hot-rolled stainless steel coated wire rod for high-strength and corrosion-resistant bridge cables according to claim 3, characterized in that: The diameter of the high carbon steel round billet is 102-106 mm; the outer diameter of the stainless steel pipe is 114-116 mm, the wall thickness is 5-6 mm, and the difference between the inner diameter of the stainless steel pipe and the diameter of the high carbon steel round billet is ≤4 mm; The welding is performed by using vacuum electron beam welding technology to weld the ends.
5. The method for preparing a hot-rolled stainless steel coated wire rod for high-strength and corrosion-resistant bridge cables according to claim 3, characterized in that: The preheating temperature of the composite steel billet is 1020-1080° C., and the preheating time is 1.5 h-2 h.
6. The method for preparing a hot-rolled stainless steel coated wire rod for high-strength and corrosion-resistant bridge cables according to claim 3, characterized in that: During the hot rolling process, oval rollers and round-hole rollers are used alternately in sequence, the oval rollers are used for the first time, and the number of passes is controlled to be an even number, and the round-hole rollers are finally used to end the rolling process; The hot rolling process adopts a horizontal-vertical alternating non-twist rolling mill.
7. The method for preparing a hot-rolled stainless steel coated wire rod for high-strength corrosion-resistant bridge cables according to claim 3 or 6, characterized in that: The hot rolling is sequentially composed of four stages: rough rolling, intermediate rolling, pre-finishing rolling and finishing rolling. The number of passes in any stage is an even number, wherein the number of passes of the rough rolling is 4-6, and the total deformation amount during the rough rolling is controlled to be 34-36%. The number of passes of the intermediate rolling is 6-8, and the total deformation amount during the intermediate rolling is controlled to be 53-55%. The number of passes of the pre-finishing rolling is 6-8, and the total deformation amount during the pre-finishing rolling is controlled to be 45-47%. The number of passes of the finishing rolling is 4-6, and the total deformation amount during the finishing rolling is controlled to be 34-36%. During the hot rolling, the starting rolling temperature is controlled to be 1000-1040°C, and the finishing rolling temperature is controlled to be 880-920°C.
8. The method for preparing a hot-rolled stainless steel coated wire rod for high-strength and corrosion-resistant bridge cables according to claim 3, characterized in that: The spinning temperature is 830-870°C.
9. The method for preparing a hot-rolled stainless steel coated wire rod for high-strength and corrosion-resistant bridge cables according to claim 3, characterized in that: The cooling adopts the Stelmore air cooling line, the total length of the Stelmore air cooling line is 90-100m, the roller speed is controlled at 45m / min-55m / min, and when running from the starting position to 14-16m, a total of 3 fans are configured, and the air volume of the 3 fans is 100%; when running from 14-16m to 33-37m, a total of 4 fans are configured, and the air volume of the 4 fans is 75%; when running from 33-37m to 47-52m, a total of 3 fans are configured, and the air volume of the 3 fans is 100%; from 47-52m to the end, the configured fans are not turned on.
10. The method for preparing a hot-rolled stainless steel coated wire rod for high-strength corrosion-resistant bridge cables according to claim 3 or 9, characterized in that: During the cooling, the heat preservation cover is fully opened and the Jialing device is 10%.
Citation Information
Cited By
Rolling method of high-carbon hard wire rod
CN120619050A